Distribution of Putative Virulence Genes and Antimicrobial Drug Resistance in Vibrio harveyi - Parvathi, Ammini (Springer-Verlag, 2011)
The marine-estuarine bacterium Vibrio harveyi is an important pathogen of invertebrates, most significantly, the larvae of commercially important shrimp Penaeus monodon. In this study, we analyzed V. harveyi isolated from shrimp hatchery environments for understanding the distribution of putative virulence genes and antimicrobial drug resistance. The putative genes targeted for PCR detection included four reversible toxin (Rtx)/hemolysin genes, a gene encoding homologue of Vibriocholerae zonula occludens toxin (Zot) and a hemolysin-coregulated protein gene (hcp) by polymerase chain reaction (PCR). Of the four putative reversible toxin genes, vhh-1 was detected in 31% of the isolates, vhh-2 in 46%, vhh-3 in 23% and vhh-4 was detected in 27% of the isolates. A zot-like sequence of bacteriophage f237 was present in 15%, while hcp sequence was detected in 48% of the isolates. The antimicrobial susceptibility test revealed resistance to several groups of antibiotics including β-lactams, cephalosporins, macrolides, quinolones, nitrofurantoin and tetracycline.